The Relationship of Standard Operating Procedures for Services at the Health Center to Community Satisfaction During the Covid-19 Pandemic in Kendari City - Prawesti, Niken; Kamalia, La Ode; Munir, Sanihu (Waluya The International Science of Health Journal, 2024)
Backgrounds: When Covid-19 became a pandemic in Indonesia, it automatically changed the face of the administrative structure and work patterns within government agencies. Starting from the term physical distancing that is applied to the work process that has shifted, from working in the office to working from home. The development of online-based service, administration and coordination processes is starting to be pursued as much as possible in each government agency environment, both central government and regional government. This is what attracted the author to conduct research on the Relationship between Standard Operating Procedures for Community Health Center Services and Community Satisfaction during the Covid-19 Pandemic in Kendari City Methods: This research is quantitative research, using a cross sectional survey approach. The population is all people who receive health services and the sample is 385 at the Kendari City Health Center. Results: The pvalue (0.038) and X2hit (6.532) were obtained, because the pvalue (0.038) < α (0.05) and the X2hit value (6.532) > Conclusion: Health center are expected to be able to provide basic health services and become pioneers in driving development in their working areas. Health center are required to provide good quality services in terms of management, resources, facilities and infrastructure so that the services provided are in accordance with standard operational procedures.